2010
DOI: 10.1242/jeb.033167
|View full text |Cite
|
Sign up to set email alerts
|

Male moths bearing transplanted female antennae express characteristically female behaviour and central neural activity

Abstract: SUMMARYThe primary olfactory centres of the sphinx moth Manduca sexta, the antennal lobes, contain a small number of sexually dimorphic glomeruli: the male-specific macroglomerular complex and the large female glomeruli. These glomeruli play important roles in sex-specific behaviours, such as the location of conspecific females and the selection of appropriate host plants for oviposition. The development of sexually dimorphic glomeruli depends strictly on the ingrowth of sex-specific olfactory receptor cell af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A second AL subsystem comprises three male-specific glomeruli (the so-called macroglomerular complex) which process information about the conspecific female's sex pheromone (Figure 2B ; Christensen and Hildebrand, 1987 ; Heinbockel et al, 1999 , 2004 ). Females have a pair of large female-specific glomeruli (LFGs, Figures 2B,C , 4A,B ) which respond to particular host plant VOCs (Roche King et al, 2000 ; Reisenman et al, 2004 ) and are involved in mediating oviposition behavior (Kalberer et al, 2010 ), and three smaller female-specific glomeruli (Grosse-Wilde et al, 2011 ). Correspondingly, three male-specific and five female-specific OR genes have been described in M. sexta (Grosse-Wilde et al, 2011 ).…”
Section: The Moth Olfactory Pathwaymentioning
confidence: 99%
“…A second AL subsystem comprises three male-specific glomeruli (the so-called macroglomerular complex) which process information about the conspecific female's sex pheromone (Figure 2B ; Christensen and Hildebrand, 1987 ; Heinbockel et al, 1999 , 2004 ). Females have a pair of large female-specific glomeruli (LFGs, Figures 2B,C , 4A,B ) which respond to particular host plant VOCs (Roche King et al, 2000 ; Reisenman et al, 2004 ) and are involved in mediating oviposition behavior (Kalberer et al, 2010 ), and three smaller female-specific glomeruli (Grosse-Wilde et al, 2011 ). Correspondingly, three male-specific and five female-specific OR genes have been described in M. sexta (Grosse-Wilde et al, 2011 ).…”
Section: The Moth Olfactory Pathwaymentioning
confidence: 99%
“…In Manduca sexta, transplanting the nascent male sensory apparatus (his antennae) to a female larva induces male development in the female brain, and the adult animal has male behaviors (Schneiderman et al, 1986). The reciprocal switch generates an animal that has female behaviors (Kalberer et al, 2010). In this case, a difference in detection induces sexually dimorphic wiring, resulting in a difference in processing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a relationship between differences in behavior and shifts in spatial patterns (Ho et al, 2006;Linster et al, 2002) and, even more, changing locations of glomeruli in mice can result in behavioral impairments, in spite of persistent physiological activations (Adam and Mizrahi, 2010). Similarly, in the AL of female moths, glomeruli in a sexually dimorphic region specialize in odorants that are related to oviposition (Kalberer et al, 2010;Reisenman et al, 2009). In Drosophila, it is known that particular glomeruli mediate appetitive and aversive behavioral responses (Semmelhack and Wang, 2009).…”
Section: Physiologymentioning
confidence: 99%